2020
DOI: 10.1136/bmjgh-2020-002306
|View full text |Cite
|
Sign up to set email alerts
|

Combating hepatitis B and C by 2030: achievements, gaps, and options for actions in China

Abstract: China has the highest number of hepatitis B and C cases globally. Despite remarkable achievements, China faces daunting challenges in achieving international targets for hepatitis elimination. As part of a large-scale project assessing China’s progress in achieving health-related Sustainable Development Goals using quantitative, qualitative data and mathematical modelling, this paper summarises the achievements, gaps and challenges, and proposes options for actions for hepatitis B and C control. China has made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…We, therefore, attribute the main decline in the incidence and mortality of hepatitis A in China to the increased use of vaccination, as described previously [9]. To reduce the burden of liver diseases caused by the different hepatitis viruses, the Chinese government has continuously increased investments in prevention and control measures for prevention of infections by HAV [34], hepatitis B virus and hepatitis C virus [35]. Based on our ITS analysis, the incidence and mortality of hepatitis A significantly decreased after inclusion of hepatitis A vaccine in EPI (the average incidence of hepatitis A was 2.1617/100 000 and decreased by an average rate of 0.2571/100 000 per year), showing the EPI strategy had a continuous effect on the decreasing trend of hepatitis A burden.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, attribute the main decline in the incidence and mortality of hepatitis A in China to the increased use of vaccination, as described previously [9]. To reduce the burden of liver diseases caused by the different hepatitis viruses, the Chinese government has continuously increased investments in prevention and control measures for prevention of infections by HAV [34], hepatitis B virus and hepatitis C virus [35]. Based on our ITS analysis, the incidence and mortality of hepatitis A significantly decreased after inclusion of hepatitis A vaccine in EPI (the average incidence of hepatitis A was 2.1617/100 000 and decreased by an average rate of 0.2571/100 000 per year), showing the EPI strategy had a continuous effect on the decreasing trend of hepatitis A burden.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges have negative impacts on research attention, public awareness and health policy maker considerations and can result in underfunding. Although China has released national action plans for the control of viral hepatitis that set clear targets for prevention, 9 aspects of fatty liver disease policy are either less well articulated than those for other liver diseases and related metabolic comorbidities (such as diabetes and cardiovascular disease) or are not articulated at all. In the field of gastrointestinal research, China has achieved admirable progress.…”
Section: The Burden Of Nafld In Chinamentioning
confidence: 99%
“…It is reported that the number of people infected with hepatitis B worldwide is approximately 250 million, and 500,000 people die every year from the complications of this disease [ 8 ]. In China, more than 93 million people are carriers of the hepatitis B virus, and about 20 million of them have chronic hepatitis B virus infection [ 9 ].…”
Section: Introductionmentioning
confidence: 99%